Kosa Kata yang Berhubungan dengan Gender dalam Bahasa Inggris dan Batak Toba (Analisis Kontrastif) - Peronika Silitonga, Dewi; Aneke Juneke Rattu, Jultje; Wallidaeny, Firdaus (Linguistika Kultura, 2026)
This research to identify and classify gender related to vocabulary in English and Batak Toba language and to analyze the differences and similarities in English and Batak Toba language. This research use descriptive qualitatif methods, to analyze data the author uses Trudgil’s theory (1974), and Lado’s theory (1957). This research found gender-related vocabulary in English and Batak Toba consists of masculine, feminine, and neutral vocabulary in the context of occupations, nouns, terms of address, adjectives, pronouns, and animals. This research provide theoretical benefits for the development of linguistics, as well as being a source of information for readers interested in this field. This research provides a new approach in documenting and maintaining local languages. This research can be a reference for further research, especially in the field of ethnolinguistics.